Reinforced aluminum silicate zirconium-containing ceramic fiber as well as preparation method and application thereof

By adjusting the content of silica, aluminum trioxide and zirconium oxide in the ceramic fibers to form a stable crystal structure, the problem of excessive shrinkage of ceramic fibers in the thickness direction at high temperatures is solved, and the quality and performance of the fibers are improved.

CN120231144APending Publication Date: 2025-07-01山西阿拉丁新材料有限公司 +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510419557.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-03
Publication Date
2025-07-01

AI Technical Summary

Technical Problem

The shrinkage rate of existing ceramic fibers in the thickness direction is too large under high temperature environments, which affects its thermal insulation and insulation properties.

Method used

By adjusting the content of silica, aluminum trioxide and zirconia, a stable crystal structure is formed, which enhances the rigidity of the fiber and inhibits the shrinkage of the fiber at high temperatures.

Benefits of technology

It effectively reduces the thickness shrinkage of ceramic fibers in high temperature environments, and improves the quality and performance of fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a reinforced aluminum silicate zirconium-containing ceramic fiber and a preparation method and application thereof, and belongs to the technical field of inorganic materials, the aluminum silicate zirconium-containing ceramic fiber is characterized by comprising the following chemical components: 49-54 wt% of SiO2, 29-34 wt% of Al2O3 and 15-20 wt% of ZrO2, the preparation method of the aluminum silicate zirconium-containing ceramic fiber comprises the following steps: uniformly mixing quartz sand, alumina powder and zircon sand, carrying out high-temperature melting, and carrying out wire drawing on the molten material to form the ceramic fiber. According to the aluminum silicate zirconium-containing ceramic fiber, the shrinkage of the ceramic fiber in the thickness direction in a high-temperature environment is effectively improved, and the quality of the ceramic fiber is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of inorganic materials, and particularly relates to an enhanced zirconium-containing aluminosilicate ceramic fiber, a preparation method thereof, and an application thereof. Background Art

[0002] Ceramic fiber is a fibrous lightweight refractory material, which has the advantages of light weight, high temperature resistance, good thermal stability, low thermal conductivity, small specific heat, and resistance to mechanical vibration, etc., and thus has been widely used in industries such as machinery, metallurgy, chemical industry, petroleum, ceramics, glass, and electronics.

[0003] With the requirements for ceramic fibers in high-temperature fields, there has emerged a zirconium-containing aluminosilicate ceramic fiber with alumina powder and quartz sand as the main raw materials and adding components such as zirconia, which improves the temperature resistance of the ceramic fiber, enables the ceramic fiber to be applicable to high temperatures of 1350 °C, and expands the application field of the ceramic fiber.

[0004] In the existing tests of the thermal stability of ceramic fibers, only the detection of the planar linear shrinkage rate, that is, the permanent heating linear change rate, is required. However, through the feedback from downstream customers, even if the planar linear shrinkage rate meets the quality standard requirements, the thickness radial linear change rate is still too large, which also affects the heat insulation and heat preservation performance of the ceramic fiber. Summary of the Invention

[0005] In order to solve the problems in the prior art, the present invention provides an enhanced zirconium-containing aluminosilicate ceramic fiber, a preparation method thereof, and an application thereof.

[0006] The first aspect of the present invention is to provide an enhanced zirconium-containing aluminosilicate ceramic fiber, and the following technical solution is adopted: An enhanced zirconium-containing aluminosilicate ceramic fiber, wherein the chemical components of the ceramic fiber are SiO2: 49-54 wt%, Al2O3: 29-34 wt%, and ZrO2: 15-20 wt%.

[0007] By adopting the above technical solution, the present application can form a stable crystal structure inside the ceramic fiber by reasonably adjusting and controlling the contents of silicon dioxide, aluminum oxide, and zirconia, enhance the rigidity of the fiber, inhibit the shrinkage of the fiber at high temperatures, thereby improving the shrinkage of the ceramic fiber in the thickness direction under high-temperature environments, and ensuring the quality of the ceramic fiber.

[0008] In a preferred embodiment, SiO2 in the ceramic fiber is 50-52 wt%.

[0009] By adopting the above technical solution, the addition of silica in the ceramic fiber helps in the formation and structural stability of the ceramic fiber. At the same time, it can control the pore size and distribution of the ceramic fiber, thereby affecting the heat insulation and fire resistance properties of the ceramic fiber. However, when the addition amount of silica is too much, it will increase the shrinkage of the ceramic fiber at high temperature. The reason is that silica is easily softened at high temperature, resulting in the relaxation of the ceramic fiber structure and increasing the probability of shrinkage. Therefore, in this application, when the addition amount of silica is further limited within the range of 50 - 52%, it can effectively ensure other properties of the ceramic fiber while reducing the shrinkage rate of the ceramic fiber in a high-temperature environment.

[0010] In a preferred embodiment, the Al2O3 in the ceramic fiber is 30 - 32 wt%.

[0011] By adopting the above technical solution, aluminum oxide in the ceramic fiber has relatively important effects on the mechanical strength, high-temperature resistance, and chemical stability of the fiber. When the addition amount of aluminum oxide is too much, although the shrinkage rate of the ceramic fiber is reduced, since aluminum oxide will hinder the movement and rearrangement of particles inside the fiber, the flexibility of the ceramic fiber is reduced and the brittleness is increased; when the addition amount of aluminum oxide is too little, the mechanical strength and high-temperature resistance of the ceramic fiber are reduced, and at the same time, a large shrinkage will also occur. This is because too little aluminum oxide will make the particles inside the fiber easier to move and rearrange, so the shrinkage rate is large. Therefore, in this application, when the content of aluminum oxide is further controlled within the range of 30 - 32 wt%, it can ensure the mechanical properties and high-temperature resistance of the ceramic fiber while reducing the shrinkage rate of the ceramic fiber.

[0012] In a preferred embodiment, the ZrO2 in the ceramic fiber is 17 - 18 wt%.

[0013] By adopting the above technical solution, when the addition amount of zirconia is too much, since it can hinder the movement and rearrangement of particles inside the ceramic fiber, the shrinkage rate of the ceramic fiber at high temperature is reduced. However, the addition of too much zirconia increases the brittleness of the fiber and reduces the flexibility of the fiber. Similarly, when the addition amount of zirconia is too little, the particles inside the ceramic fiber are easier to move and rearrange, resulting in a large shrinkage rate of the ceramic fiber. Therefore, in this application, by further optimizing the addition amount of zirconia, the mechanical properties of the ceramic fiber are effectively ensured and the shrinkage rate of the ceramic fiber is reduced.

[0014] The second aspect of the present invention is to provide a preparation method of the above-mentioned enhanced aluminosilicate zirconium-containing ceramic fiber, including the following steps: uniformly mixing quartz sand, alumina powder, and zircon sand, then performing high-temperature melting, and then drawing the molten material into ceramic fibers.

[0015] In a preferred embodiment, the melting temperature is 1750 - 1850 °C.

[0016] The third aspect of the present invention is to provide an application of the above-mentioned enhanced zirconium-containing aluminosilicate ceramic fiber. 80 - 87 wt% of the enhanced zirconium-containing aluminosilicate ceramic fiber is mixed with 13 - 20 wt% of polycrystalline alumina fiber to produce zirconium-containing aluminosilicate ceramic fiber with a classification temperature of 1515 °C without chromium.

[0017] In summary, the present invention has the following beneficial effects: By reasonably adjusting and controlling the contents of silicon dioxide, aluminum oxide, and zirconium oxide, the present application can form a stable crystal structure inside the ceramic fiber, enhance the rigidity of the fiber, and inhibit the shrinkage of the fiber at high temperatures, thereby reducing the shrinkage of the ceramic fiber in the thickness direction in a high-temperature environment and ensuring the quality of the ceramic fiber. Detailed Embodiments

[0018] The present invention will be further described in detail below with reference to embodiments. All reagents without indicating the manufacturer are conventional reagent products that can be obtained through commercial purchase.

[0019] In some specific embodiments of zirconium-containing aluminosilicate ceramic fiber, the chemical composition of the ceramic fiber is SiO2: 49 - 54 wt%, Al2O3: 29 - 34 wt%, ZrO2: 15 - 20 wt%.

[0020] In some specific embodiments of zirconium-containing aluminosilicate ceramic fiber, more preferably, the SiO2 in the ceramic fiber is 50 - 52 wt%.

[0021] In some specific embodiments of zirconium-containing aluminosilicate ceramic fiber, more preferably, the Al2O3 in the ceramic fiber is 30 - 32 wt%.

[0022] In some specific embodiments of zirconium-containing aluminosilicate ceramic fiber, more preferably, the ZrO2 in the ceramic fiber is 17 - 18 wt%.

[0023] In some specific embodiments of zirconium-containing aluminosilicate ceramic fiber, using the above raw materials and according to the following preparation method, quartz sand, alumina powder, and zircon sand are mixed evenly and then subjected to high-temperature melting, and then the molten material is drawn into ceramic fiber.

[0024] In some specific embodiments of zirconium-containing aluminosilicate ceramic fiber, the melting temperature is 1750 - 1850 °C.

[0025] In some specific embodiments of the zirconium-containing aluminosilicate ceramic fiber, the obtained zirconium-containing aluminosilicate ceramic fiber is applied to the production of zirconium-containing aluminosilicate ceramic fiber with a non-chromium classification temperature of 1515°C. Specifically, 75-90 wt% of the enhanced zirconium-containing aluminosilicate ceramic fiber can be mixed with 10-25 wt% of polycrystalline alumina fiber to produce zirconium-containing aluminosilicate ceramic fiber with a non-chromium classification temperature of 1515°C.

[0026] Based on the above content, this application will prove the influence of the raw material dosage on the shrinkage rate of ceramic fiber through the following several examples and comparative examples. Example 1

[0027] A preparation method of enhanced zirconium-containing aluminosilicate ceramic fiber includes the following steps: According to the chemical composition of the ceramic fiber being SiO2: 49 wt%, Al2O3: 34 wt%, ZrO2: 17 wt%, mix quartz sand, alumina powder, and zircon sand evenly and then add them into a resistance furnace for high-temperature melting at a temperature of 1750°C. Then, spin the molten liquid into fibers through a high-speed spinning machine; Then spread the fibers into a continuous cotton blank in a cotton collecting box. Finally, subject the fiber cotton blank to needling and high-temperature calcination for shaping to make a fiber blanket, and then detect the shrinkage performance of the fiber blanket. Example 2

[0028] A preparation method of enhanced zirconium-containing aluminosilicate ceramic fiber includes the following steps: According to the chemical composition of the ceramic fiber being SiO2: 50 wt%, Al2O3: 34 wt%, ZrO2: 16 wt%, mix quartz sand, alumina powder, and zircon sand evenly and then add them into a resistance furnace for high-temperature melting at a temperature of 1750°C. Then, spin the molten liquid into fibers through a high-speed spinning machine; Then spread the fibers into a continuous cotton blank in a cotton collecting box. Finally, subject the fiber cotton blank to needling and high-temperature calcination for shaping to make a fiber blanket, and then detect the shrinkage performance of the fiber blanket. Example 3

[0029] A preparation method of enhanced zirconium-containing aluminosilicate ceramic fiber includes the following steps: According to the chemical composition of the ceramic fiber being SiO2: 52 wt%, Al2O3: 30 wt%, ZrO2: 18 wt%, mix quartz sand, alumina powder, and zircon sand evenly and then add them into a resistance furnace for high-temperature melting at a temperature of 1750°C. Then, spin the molten liquid into fibers through a high-speed spinning machine; Then spread the fibers into a continuous cotton blank in a cotton collecting box. Finally, subject the fiber cotton blank to needling and high-temperature calcination for shaping to make a fiber blanket, and then detect the shrinkage performance of the fiber blanket. Example 4

[0030] A preparation method of enhanced zirconium-containing aluminosilicate ceramic fiber, comprising the following steps: According to the chemical composition of the ceramic fiber being SiO2: 54 wt%, Al2O3: 29 wt%, ZrO2: 17 wt%, mix quartz sand, alumina powder, and zircon sand evenly, then add them into a resistance furnace and carry out high-temperature melting at a temperature of 1750 °C, and then spin the molten liquid into fibers through a high-speed spinning machine; Then spread the fibers into a continuous cotton blank on a cotton collecting box, and finally subject the fiber cotton blank to needling and high-temperature calcination for shaping to make a fiber blanket, and then detect the shrinkage performance of the fiber blanket. Example 5

[0031] A preparation method of enhanced zirconium-containing aluminosilicate ceramic fiber, comprising the following steps: According to the chemical composition of the ceramic fiber being SiO2: 50 wt%, Al2O3: 30 wt%, ZrO2: 20 wt%, mix quartz sand, alumina powder, and zircon sand evenly, then add them into a resistance furnace and carry out high-temperature melting at a temperature of 1750 °C, and then spin the molten liquid into fibers through a high-speed spinning machine; Then spread the fibers into a continuous cotton blank on a cotton collecting box, and finally subject the fiber cotton blank to needling and high-temperature calcination for shaping to make a fiber blanket, and then detect the shrinkage performance of the fiber blanket. Example 6

[0032] A preparation method of enhanced zirconium-containing aluminosilicate ceramic fiber, comprising the following steps: According to the chemical composition of the ceramic fiber being SiO2: 53 wt%, Al2O3: 32 wt%, ZrO2: 15 wt%, mix quartz sand, alumina powder, and zircon sand evenly, then add them into a resistance furnace and carry out high-temperature melting at a temperature of 1750 °C, and then spin the molten liquid into fibers through a high-speed spinning machine; Then spread the fibers into a continuous cotton blank on a cotton collecting box, and finally subject the fiber cotton blank to needling and high-temperature calcination for shaping to make a fiber blanket, and then detect the shrinkage performance of the fiber blanket. Example 7

[0033] A preparation method of enhanced zirconium-containing aluminosilicate ceramic fiber, different from Example 1 in that the high-temperature melting temperature is 1850 °C, and the others are the same as in Example 1. Comparative Example 1

[0034] A ceramic fiber disclosed in Chinese Patent CN105523718A, with its chemical composition being: SiO2: 40 wt%, Al2O3: 45 wt%, ZrO2: 15 wt%. Comparative Example 2

[0035] A preparation method of enhanced zirconium-containing aluminosilicate ceramic fibers, which is different from that of Example 1 in that the composition content of the ceramic fibers is different from that of Example 1. The specific composition content is: SiO2: 56 wt%, Al2O3: 25 wt%, ZrO2: 19 wt%, and the others are the same as those of Example 1. Comparative Example 3

[0036] A preparation method of enhanced zirconium-containing aluminosilicate ceramic fibers, which is different from that of Example 1 in that the composition content of the ceramic fibers is different from that of Example 1. The specific composition content is: SiO2: 49 wt%, Al2O3: 32 wt%, ZrO2: 17 wt%, yttrium oxide 2 wt%, and the others are the same as those of Example 1. Performance detection

[0037] The fiber blankets prepared in the above examples and comparative examples were detected for the change rate at high temperature and the tensile strength at room temperature. The detection results are shown in Table 1.

[0038] Table 1 Detection results of fiber blankets in the examples and comparative examples of this application

[0039] It can be seen from Table 1 that the plane change rates of the ceramic fiber blankets obtained in Examples 1-6 of this application are all less than 1.8% under the condition of 1400 °C, and the thickness change rates are all less than 6.0% under the condition of 1400 °C. This shows that after adjusting the contents of silicon oxide, aluminum oxide and zirconium oxide in this application, the shrinkage rate of the ceramic fiber blanket in the thickness direction can be effectively controlled, and the quality of the ceramic fiber is improved.

[0040] Compared with Example 1, in Comparative Examples 1-2, when the addition amounts of silicon oxide and aluminum oxide are not within the ranges defined in this application, the plane shrinkage rates of the ceramic fiber blankets obtained in Comparative Examples 1-2 are all above 3% at 1400 °C, and the change rate in the thickness direction is significantly increased compared with Example 1. It can be further explained that when the contents of silicon oxide and aluminum oxide in this application are within the ranges defined in this application, the shrinkage performance of the ceramic fiber in the width direction can be effectively guaranteed.

[0041] Comparing Comparative Example 3 with Example 1, when the contents of silicon oxide and aluminum oxide are both within the scope of the present application, it is found that by adding 2 wt% of yttrium oxide to the ceramic fiber, the planar change rate and thickness change rate of the zirconium-containing aluminosilicate ceramic fiber in Comparative Example 3 at 1400 °C are not lower than those in Example 1. Moreover, when the present inventors detected the high-temperature stability under the condition of 1500 °C × 24 h, it was found that the planar change rate and thickness change rate in Comparative Example 3 are much higher than those in Example 1. It can be seen that the addition of yttrium oxide not only does not improve the stability of the ceramic fiber at high temperature, but instead increases the shrinkage rate of the ceramic fiber at high temperature. Therefore, it can be further explained that after reasonably adjusting the contents of aluminum oxide, silicon oxide and zirconium oxide in the present application, the stability of the zirconium-containing aluminosilicate ceramic fiber at high temperature is effectively improved. Compared with adding other raw materials to the ceramic fiber, the formulation cost of the present application is lower and it also has excellent high-temperature stability. Application Example

[0042] The fibers obtained in the above Example 3 and Comparative Example were mixed with polycrystalline alumina fibers to produce a zirconium-containing aluminosilicate ceramic fiber with a classification temperature of 1515 °C without chromium, and then the planar linear shrinkage rate of the ceramic fiber was detected. The detection results are shown in Table 2.

[0043] Table 2 Detection Results of Zirconium-Containing Aluminosilicate Ceramic Fiber with a Classification Temperature of 1515 °C without Chromium As can be seen from Table 2, the planar linear shrinkage rate of the zirconium-containing aluminosilicate ceramic fiber with a classification temperature of 1515 °C produced by using the ceramic fiber obtained in the present application in combination with polycrystalline alumina fibers is less than 2.0% at 1500 °C, while the planar linear shrinkage rate of the zirconium-containing aluminosilicate ceramic fiber with a classification temperature of 1515 °C produced by using the ceramic fibers obtained in Comparative Example 1, Comparative Example 2 and Comparative Example 3 is above 5% at 1500 °C, which further illustrates that the contents of aluminum oxide and silicon oxide have a significant impact on the quality of the ceramic fiber.

[0044] The embodiments of this specific implementation manner are all preferred embodiments of the present invention, and do not limit the protection scope of the present invention accordingly. Therefore, all equivalent changes made according to the structure, shape and principle of the present invention should be covered within the protection scope of the present invention.

Claims

1. A reinforced aluminum silicate zirconium-containing ceramic fiber, characterized in that: The chemical composition of the ceramic fiber is SiO2: 49-54wt%, Al2O3: 29-34wt%, and ZrO2: 15-20wt%.

2. The reinforced aluminum silicate zirconium-containing ceramic fiber according to claim 1, characterized in that: The SiO2 content in the ceramic fiber is 50-52wt%.

3. The reinforced aluminum silicate zirconium-containing ceramic fiber according to claim 1 or 2, characterized in that: The Al2O3 content in the ceramic fiber is 30-32wt%.

4. The reinforced aluminum silicate zirconium-containing ceramic fiber according to claim 1 or 2, characterized in that: The ZrO2 content in the ceramic fiber is 17-18 wt%.

5. A method for preparing the reinforced aluminum silicate zirconium-containing ceramic fiber according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: mixing quartz sand, alumina powder and zircon sand uniformly, melting them at high temperature, and then drawing the molten materials into ceramic fibers.

6. The method for preparing a reinforced aluminum silicate zirconium-containing ceramic fiber according to claim 5, characterized in that: The melting temperature is 1750-1850°C.

7. An application of the reinforced aluminum silicate zirconium-containing ceramic fiber according to any one of claims 1 to 4, characterized in that: 80-87wt% of the reinforced aluminum silicate zirconium-containing ceramic fiber is mixed with 13-20wt% of the polycrystalline alumina fiber to produce the aluminum silicate zirconium-containing ceramic fiber without chromium and with a classification temperature of 1515°C.

Citation Information

Patent Citations

  • Ceramic fiber and preparation method thereof and industrial furnace inner liner

    CN105523718A